Apyrase Suppression Raises Extracellular ATP Levels and Induces Gene Expression and Cell Wall Changes Characteristic of Stress Responses . Issue 4 (18th February 2014) - Lim, Min Hui; Wu, Jian; Yao, Jianchao; Gallardo, Ignacio F.; Dugger, Jason W.; Webb, Lauren J.; Huang, James; Salmi, Mari L.; Song, Jawon; Clark, Greg; Roux, Stanley J.
Abstract : Suppressing the expression of two apyrase genes raises extracellular ATP levels and induces gene expression, growth, and cell wall changes characteristic of stress responses, thus implicating extracellular nucleotides as early signals linking biotic and abiotic stresses to growth inhibition . Abstract: Plant cells release ATP into their extracellular matrix as they grow, and extracellular ATP (eATP ) can modulate the rate of cell growth in diverse tissues. Two closely related apyrases (APYs) in Arabidopsis ( Arabidopsis thaliana ), APY1 and APY2, function, in part, to control the concentration of eATP . The expression of APY1/APY2 can be inhibited by RNA interference, and this suppression leads to an increase in the concentration of eATP in the extracellular medium and severely reduces growth. To clarify how the suppression of APY1 and APY2 is linked to growth inhibition, the gene expression changes that occur in seedlings when apyrase expression is suppressed were assayed by microarray and quantitative real-time-PCR analyses. The most significant gene expression changes induced by APY suppression were in genes involved in biotic stress responses, which include those genes regulating wall composition and extensibility. These expression changes predicted specific chemical changes in the walls of mutant seedlings, and two of these changes, wall lignification and decreased methyl ester bonds, were verified by direct analyses. Taken together, the results are consistent with the hypothesis that APY1, APY2, and eATP play important roles in the signaling steps that link biotic stresses to plant defense responses and growth changes.